From unorthodox to established: the current status of 18F-trifluoroborate- and 18F-SiFA-based radiopharmaceuticals in PET nuclear imaging - Bernard-Gauthier, Vadim; Wängler, Björn; Wängler, Carmen (Bioconjugate chemistry, 2016)
Unorthodox 18F-labeling strategies not employing the formation of a carbon-18F bond are seldom found in radiochemistry. Historically, the formation of a boron- or silicon-18F bond has been introduced very early on into the repertoire of labeling chemistries, but is without translation into any clinical radiotracer besides inorganic B[18F]F4- for brain tumor diagnosis. For many decades these labeling methodologies were forgotten and have just recently been revived by a handful of researchers thinking outside the box. When breaking with established paradigms such as the inability to obtain labeled compounds of high specific activity via isotopic exchange or performing radiofluorination in aqueous media, the research community often reacts skeptically. In 2005 and 2006, two novel labeling methodologies were introduced into radiochemistry for positron emission tomography (PET) tracer development: RBF3- labeling reported by Perrin et al. and the SiFA methodology by Schirrmacher, Jurkschat, and Waengler et al. which is based on isotopic exchange (IE). Both labeling methodologies have been complemented by other noncanonical strategies to introduce 18F into biomolecules of diagnostic importance, thus profoundly enriching the landscape of 18F radiolabeling. B- and Si-based labeling strategies finally revealed that IE is a viable alternative to established and traditional radiochemistry with the advantage of simplifying both the labeling effort as well as the necessary purification of the radiotracer. Hence IE will be the focus of this contribution over other noncanonical labeling methods. Peptides for tumor imaging especially lend themselves favorably toward one-step labeling via IE, but small molecules have been described as well, taking advantage of these new approaches, and have been used successfully for brain imaging. This Review gives an account of both radiochemistries centered on boron and silicon, describing the very beginnings of their basic research, the path that led to optimization of their chemistries, and the first encouraging preclinical results paving the way to their clinical use. This side by side approach will give the reader the opportunity to follow the development of a new basic discovery into a clinically applicable radiotracer including all the hurdles that have had to be overcome.